Dilemmas in counselling: the EEC syndrome. - Tse, K (1990)
A family with the EEC syndrome is reported. Two sibs have the classical form of the condition with ectrodactyly, ectodermal dysplasia, and clefting. Their mother, however, has only minimal evidence, with preaxial polydactyly of the right hand and duplication of the terminal phalanx of the second toe of the left foot with 3/4 syndactyly. The dilemmas faced by the genetic counsellor are discussed in this variable autosomal dominant condition.